Parent Involvement in Caring for Hospitalized Preterm Infants. (December 2016) - Sarapat, P.; Fongkaew, W.; Jintrawet, U.; Mesukko, J.; Ray, L.
Abstract : Background: In Thailand, the incidence of preterm birth and the survival rates of preterm infants are rising. Many hospitals promote parent involvement in caring for their hospitalized preterm infants in order to support breastfeeding and parent-infant attachment. Little is known about Thai parents' perspectives on their involvement in caring for their preterm infants during hospitalization. Objective: This study aimed to gain a better understanding of parent involvement in caring for hospitalized preterm infants. Methods: A focused ethnographic approach was selected for this study. Purposive sampling was used to recruit 22 parents who provided care for their preterm infants during their hospitalization at the Sick Newborn Unit. Data were collected through participant observation, in-depth interviews and supplementary data sources from September 2014 to October 2015. Data were analyzed by using thematic analysis. Results: Findings revealed that parents involvement in caring for their hospitalized preterm infants, five themes emerged; 1) uncertainty about their child's condition including worrying about the child's condition, trying to seek information about their child's condition, and praying to holy things for their child's well-being, 2) unconfident in providing care for preterm babies by being afraid of their babies being at risk, having insufficient skills, and receiving insufficient information, 3) limited decision making involvement in caring by following the nurse's advice and having little chance to share information, 4) overcoming difficulties in breastfeeding including producing enough milk supply, confronting problems in breastfeeding, and desiring to bond with their babies through breastfeeding, and 5) needs for improved parent involvement regarding shared decision making and implementation of practice guidelines. Conclusion: Parent involvement in caring for hospitalized preterm infants is crucial for the outcomes of infant care. These findings could be used as baseline data for healthcare providers to effectively enhance parent involvement in caring for their preterm infants.